The northern coast of the Black Sea as a “frontier” and its role in shaping the society in Ukrainian history in the 16-18th century - Varga, Beáta (Études sur la Région Méditerranéenne, 2024)
The most significant characteristic of the northern coast of the Black Sea as “southern steppe frontier” was that the mass resettlement of the population to the southern border zone, where a voluntary border guard system was established, was mainly due to state policy and the fact that the region lacked a permanently settled population. The emergence of Cossacks was the result of a frontier-like lifestyle that evolved on Eastern European steppes. From the late 15th century, along the Dnieper, Volga and Don Rivers, in the southern borderlands, a unique community of free Cossacks was born, establishing a military democracy. To a certain extent, Cossacks could be considered a mobile frontier community with the same rights as the rest of the society. The three main differences between these Black Sea and the American frontier are: 1. The populating process taking place in the northern basin of the Black Sea from the beginning of the 16th century preceded the military takeover of the region; 2. the feudal system prevailed in the region; and 3. at the end of the 18th century, the region lost its restricted autonomy.